Search for charged lepton flavor violation in narrow upsilon decays. - Lees, J; Poireau, V; Prencipe, E; Tisserand, V; Garra Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; Eigen, G; Stugu, B; Sun, L; et al. (2010)
Charged-lepton flavor-violating processes are unobservable in the standard model, but they are predicted to be enhanced in several extensions to the standard model, including supersymmetry and models with leptoquarks or compositeness. We present a search for such processes in a sample of 99x10(6)Upsilon(2S) decays and 117x10(6)Upsilon(3S) decays collected with the BABAR detector. We place upper limits on the branching fractions B(Upsilon(nS)-->e(+/-)tau(-/+)) and B(Upsilon(nS)-->mu(+/-)tau(-/+)) (n=2,3) at the 10(-6) level and use these results to place lower limits of order 1 TeV on the mass scale of charged-lepton flavor-violating effective operators.